Muatan Nilai-Nilai Pancasila Dalam Film Hafiz dan Hafizah - Jesika Carolina; M Iqbal Arrosyad; Gatot Afrianto (Universitas Muhammadiyah Bangka Belitung, 2026)
This study aims to explain the content of Pancasila values depicted in the animated film Hafiz and Hafizah and examine their relevance to character education in elementary schools. A qualitative method with a content analysis approach was employed to systematically and objectively analyze the film's dialogues, characters, settings, and events.The results show that the film embodies social care values aligned with Pancasila's principles, such as empathy, cooperation, responsibility, helpfulness, and concern for others. Students can internalize these values as part of character formation based on national values.The film serves as an effective educational medium for developing moral and social values, thereby strengthening Pancasila-based education. Through relatable characters and everyday situations, the film effectively delivers moral messages that children can easily understand. The study concludes that animated films can serve as an effective medium for character education and are expected to influence children's attitudes and behavior positively.